ANALISIS KOMPARATIF TANAMAN PERKEBUNAN DI PROPINSI RIAU - Octavianus Agustus; Masyhuri Masyhuri; Mas Soedjono (Agro Ekonomi, 1999)
Plantation crop particularly rubber, cconut and oil palm are important export commodities because they are reliable to increase the foreign exchange and plantation farmers income.